Educational philosophy of Mahatma Gandhi - Singh, Y.K. (New delhi : APH Publication)
Given Gandhi's Values and his Vision of what constituted a truly civilized and free India, it was not surprising that he developed firm Views on education. Education not only moulds the new generation, but reflects a society's fundamental assumption.
Includes references.
Keywords: Gandhi, -- Mahatma -- 1869-1948.; Education -- Philosophy; Education -- India